A Brønsted Acidic Gallium Hydride: Facile Interconversion of NNNN‐Macrocycle Supported [GaI]+ and [GaIIIH]2+. Issue 11 (27th January 2022) - Morris, Louis J.; Ghana, Priyabrata; Rajeshkumar, Thayalan; Carpentier, Ambre; Maron, Laurent; Okuda, Jun
Abstract: Protonolysis of [Cp*M] (M=Ga, In, Tl) with [(Me4 TACD)H][BAr4 Me ] (Me4 TACD= N, N′, N′′, N′′′ ‐tetramethyl‐1, 4, 7, 10‐tetraazacyclododecane; [BAr4 Me ] − =[BC6 H3 ‐3, 5‐(CH3 )2 4 ] − ) provided monovalent salts [(Me4 TACD)M][BAr4 Me ], whereas [Cp*Al]4 yielded trivalent [(Me4 TACD)AlH][BAr4 Me ]2 . Protonation of [(Me4 TACD)Ga][BAr4 Me ] with [Et3 NH][BAr4 Me ] gave an unusually acidic (p K a (CH3 CN)=24.5) gallium(III) hydride dication [(Me4 TACD)GaH][BAr4 Me ]2 . Deprotonation with IMe4 (1, 3, 4, 5‐tetramethyl‐imidazol‐ylidene) returned [(Me4 TACD)Ga][BAr4 Me ]. These reversible processes occur with formal two‐electron oxidation and reduction of gallium. DFT calculations suggest that gallium(I) protonation is facilitated by strong coordination of the tetradentate ligand, which raises the HOMO energy. High nuclear charge of [(Me4 TACD)GaH] 2+ facilitates hydride‐to‐metal charge transfer during deprotonation. Attempts to prepare a gallium(III) dihydride cation resulted in spontaneous dehydrogenation to [(Me4 TACD)Ga] + . Abstract : Protonation of an NNNN‐macrocycle chelated gallium(I) cation provides a rare dicationic gallium(III) hydride. This process is easily reversed by treatment of the Brønsted acidic (p K a =24.5) hydride with a neutral base. Similar facile redox cycling was not observed for analogous aluminium, indium, or thallium systems.